Implementasi Kurikulum Merdeka Terhadap Efektifitas Mata Pelajaran Pendidikan Agama Islam Kelas X di MA Al-Muthmainnah Leseng - Winata, Andri; Parhun, Muhammad; Agus Sofiyandi, Muji (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2024)
This research examines the implementation of the transition Merdeka Curriculum in the context of Islamic Religious Education learning at MA Al-Muthmainnah Leseng. The purpose of this study is to analyze the effectiveness of these curriculum changes on the Islamic Education learning process, identify challenges faced by teachers and students, and evaluate their impact on student learning outcomes. The research employs a descriptive qualitative method with data collection through observation, interviews, and documentation studies. The results indicate that the implementation of the Merdeka Curriculum provides greater flexibility in Islamic Education learning, although it requires significant adjustments from educators. The project-based learning and student-centered approach promoted by the Merdeka Curriculum have proven to increase student engagement in Islamic Education learning. However, several obstacles were identified, such as limited teacher understanding of new concepts and students' need to adapt to more independent learning methods. This research provides recommendations for improving teacher competencies and providing supporting infrastructure in implementing the Merdeka Curriculum.